The PHEMU21 catalogue and astrometric results of the observations of the mutual occultations and eclipses of the Galilean satellites of Jupiter made in 2021. Issue 3 (8th September 2022) - Emelyanov, N; Arlot, J-E; Anbazhagan, P; André, P; Bardecker, J; Canaud, G; Coliac, J F; De Elias Cantalapiedra, J; Ellington, C K; Fernandez, J M; Forbes, M; Gazeas, K; et al.
ABSTRACT: 2021 was the year of Jupiter's equinox, that is the Sun and the Earth passed through the equatorial plane of the planet and therefore the orbital planes of its main satellites. This occurrence made it possible to observe mutual occultations and eclipses between the satellites. Our former experience shows that observations of such events provide accurate astrometric data that can be used to obtain new information on the dynamics of the Galilean satellites. The observations are a series of photometric measurements of a satellite which are carried out through the organization of a world wide campaign of observations thus maximizing the number and the quality of the data obtained. This work focuses on processing the photometric observations of the mutual occultations and eclipses of the Galilean satellites of Jupiter made during the international campaign in 2021. The final goal is to derive new accurate astrometric data. We used an accurate photometric model of mutual events in conjunction with the accuracy of observation. We obtained and processed the 84 light curves obtained during the campaign. As compared with the current best ephemerides, the rms of 'O–C' residuals are equal to 49 and 48 mas in right ascension and declination, respectively.